Healthy eating interventions delivered in the family home: A systematic review. (1st September 2019) - Snuggs, Sarah; Houston-Price, Carmel; Harvey, Kate
Abstract: Unhealthy eating habits have long term health implications and can begin at a young age when children still consume the majority of their meals at home. As parents are the principal agents of change in children's eating behaviours, the home environment is the logical location for the delivery of interventions targeting healthy family eating. Despite the recent proliferation of published studies of behaviour-change interventions delivered in the home, there has been little attempt to evaluate what makes such interventions successful. This review provides a systematic evaluation of all healthy eating interventions delivered to families in the home environment to date and seeks to identify the successful elements of these interventions and make recommendations for future work. Thirty nine studies are described, evaluated and synthesised. Results show that evidence- and theory-based interventions tended to be more successful than those that did not report detailed formative or evaluative work although details of theory application were often lacking. Careful analysis of the results did not show any further systematic similarities shared by successful interventions. Recommendations include the need for more clearly theoretically driven interventions, consistent approaches to measuring outcomes and clarity regarding target populations and desired outcomes.